Effects of dietary dandelion extract on the growth performance, serum biochemical parameters, liver histology, and immune and apoptosis-related genes expression of hybrid grouper (Epinephelus lanceolatus♂ × Epinephelus fuscoguttatus♀) at different feeding period. Issue 120 (January 2022) - Sun, Zhenzhu; Tan, Xiaohong; Wei, Zonglu; Liu, Qingying; Mai, Haobin; Liu, Yang; Liu, Bo; Zhuang, Yutong; Zou, Danyang; Zhang, Wenqiang; Liu, Xinting; Ye, Chaoxia
Abstract: The study explored on the effects of dietary 0.4% dandelion extract on the growth performance, serum biochemical parameters, liver histology and the expression levels of immune and apoptosis-related genes in the head kidney and spleen of hybrid grouper ( Epinephelus lanceolatus ♂ × Epinephelus fuscoguttatus ♀) at different feeding period. The results showed that the weight gain rate (WGR) of the hybrid grouper were significantly increased at the second and fourth weeks ( P < 0.05), but there was no significant difference in WGR at the eighth week ( P > 0.05). Compared with the control group, dietary dandelion extracts supplementation improve lipid metabolism, reduce lipid accumulation in liver and maintain normal liver histology at the second and fourth weeks. At the end of the second week, the relative expression levels of antioxidant related genes (MnSOD, GPX and GR) in the head kidney of hybrid grouper fed with dandelion extract increased significantly; at the end of week 4 and week 8, the relative expression levels of antioxidant related genes other than MnSOD did not change significantly. However, in the spleen of hybrid grouper, the expression of these antioxidant genes showed the opposite trend. At the end of the eighth week, dietary dandelion extract supplementation significantly increased the expression of inflammatory response related genes in head kidney of hybrid grouper, but showed the opposite trend in spleen. In conclusion, the short-term (2 or 4 weeks) application of 0.4% dandelion extract in feed had the effects of growth improvement, liver protection and immune stimulation on hybrid grouper due to its antioxidant and anti-inflammatory activities. The beneficial effect of dandelion extract on hybrid grouper was time-dependent, and its action time on different immune organs of hybrid grouper was not synchronous. Highlights: Short-term application of 0.4% dandelion extract (DE) in feed could significantly improve the weight gain rate of hybrid grouper. Dietary DE supplementation could protect liver and reduce the accumulation of liver fat. The beneficial effect of DE on hybrid grouper was time-dependent, and its optimum use time was 2–4 weeks.